Setting the chaperonin timer: The effects of K(+) and substrate protein on ATP hydrolysis - Grason, John P. (National Academy of Sciences, 2008)
The effects of potassium ion on the nested allostery of GroEL are due to increases in the affinity for nucleotide. Both positive allosteric transitions, TT-TR and TR-RR, occur at lower [ATP] as [K(+)] is increased. Negative cooperativity in the double-ringed system is also due to an increase in the affinity of the trans ring for the product ADP as [K(+)] is increased. Consequently, (i) rates of ATP hydrolysis are inversely proportional to [K(+)] and (ii) the residence time of GroES bound to the cis ring is prolonged and the hemicycle time extended. Substrate protein suppresses negative cooperativity by decreasing the affinity of the trans ring for ADP, reducing the hemicycle time to a constant minimum. The trans ring thus serves as a variable timer. ATP added to the asymmetric GroEL-GroES resting-state complex lacking trans ring ADP is hydrolyzed in the newly formed cis ring with a presteady-state burst of ≈6 mol of Pi per mole of 14-mer. No burst is observed when the trans ring contains ADP. The amplitude and kinetics of ATP hydrolysis in the cis ring are independent of the presence or absence of encapsulated substrate protein and independent of K(+) at concentrations where there are profound effects on the linear steady-state rate. The hydrolysis of ATP by the cis ring constitutes a second, nonvariable timer of the chaperonin cycle.